Toward a local wisdom-based organizational culture model: A grounded theory study of Galuh values - Nana Darna Darna; Aan Suryana; Dindin Herdiansah; Wahyu Wahyudin (Interdisciplinary International Journal of Conservation and Culture, 2026)
This study aims to develop a local wisdom-based organizational culture model through a Grounded Theory approach by examining the internalization of Galuh cultural values: Silih Asah, Silih Asih, Silih Asuh, and Silih Wangi. Data were collected through in-depth interviews, non-participant observations, and document analysis involving employees, organizational leaders, and students at Universitas Galuh. The analysis followed systematic Grounded Theory procedures, including open coding, axial coding, and selective coding, supported by constant comparative methods and iterative analysis until theoretical saturation was achieved. The findings indicate that the internalization of Galuh values fosters knowledge sharing, strengthens empathetic interpersonal relationships, supports mentoring practices, and enhances professional and ethical behavior. These elements collectively contribute to the formation of a harmonious, adaptive, and sustainable organizational culture. However, the degree of internalization varies across individuals due to differences in perception, background, and organizational commitment, highlighting the dynamic nature of cultural adoption. Furthermore, while these values help reduce interpersonal conflict, they do not eliminate it, but instead provide a constructive framework for conflict management. This study contributes to the literature by proposing a substantive model of organizational culture grounded in local wisdom, offering a strategic framework for integrating cultural values into organizational systems to improve employee behavior, organizational effectiveness, and long-term sustainability.